2016
DOI: 10.5489/cuaj.4054
|View full text |Cite
|
Sign up to set email alerts
|

Localized prostate cancer

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Prostate cancer (PCa) continues to plague male health around the world, representing the most common malignant tumor among male patients, accompanied by the second highest mortality rate in male patients with malignant tumors 13. Studies have revealed that, in 2016, 180,890 male patients in the USA were diagnosed with PCa, and another 85,920 patients succumbed to PCa 4.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) continues to plague male health around the world, representing the most common malignant tumor among male patients, accompanied by the second highest mortality rate in male patients with malignant tumors 13. Studies have revealed that, in 2016, 180,890 male patients in the USA were diagnosed with PCa, and another 85,920 patients succumbed to PCa 4.…”
Section: Introductionmentioning
confidence: 99%
“…PCa is the leading cause of noncutaneous malignancy in US men and the second leading cause of cancer mortality in men . In 2016, it is estimated that 180 890 men will be diagnosed with PCa, and 26 120 will die of PCa .…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) represents the second most common cancer in males, with 128 cases per 100 000 men . An estimated 1.1 million new PCa cases and 307 000 PCa deaths occurred every year .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostate cancer (PCa) is the second most commonly diagnosed cancer and the fifth leading cause of cancer death in men [1,2]. An estimated 1.1 million new PCa cases and 307 thousand PCa deaths occurred in 2012 worldwide [3].…”
mentioning
confidence: 99%